The influence of oxygen on skin-core structure of polyacrylonitrile-based precursor fibers. (27th May 2020) - Sun, Lihao; Li, Ming; Shang, Lei; Xiao, Linghan; Liu, Yu; Zhang, Mengjie; Ao, Yuhui
Abstract: The influence of oxygen on the skin-core structure of polyacrylonitrile-based precursor fibers has been systemically studied using attenuated total reflection infrared spectroscopy (ATR-IR), atomic force microscopy (AFM), nanoscale infrared spectroscopy (nano-IR), X-ray, scanning electron microscopy (SEM), optical microscopy (OM) and nanoscale Lorentz contact resonance (nano-LCR). ATR-IR, AFM and nano-IR reveal the radial distribution of specific functional groups. It was found that under oxygen-sufficient conditions, many ladder aromatic rings are formed in the skin. Intermolecular crosslinking presumably occurs through oxygen-induced dehydrogenation reactions. Under oxygen-deprived conditions, large numbers of isolated aromatic rings are generated in the core. Intermolecular crosslinking is dependent on comonomer concentration. In addition, different fractured and polished morphologies of skin and core may be identified using SEM and OM, providing evidence for radial transformations of crystal structure. Moreover, the modulus distribution in the fiber as reflected by nano-LCR further supports the proposed intermolecular crosslinking and crystal rearrangement processes. Graphical abstract: Image 1 Highlights: The nano-IR spectroscopy was applied herein for illustrating structure difference of cross section of single filament. Except for the changes of skin-core chemical structure, the transformation of skin-core crystal structure was discussed. The more precise modulus distribution across the fiber cross section was obtained using the nano-LCR mapping technique.